Built-in reliability design of a high-frequency SiC MOSFET power module - Li, Jianfeng; Gurpinar, Emre; Lopez Arevalo, Saul; Castellazzi, Alberto; Mills, Liam (2014)
A high frequency SiC MOSFET-based three-phase, 2-level power module has been designed, simulated, assembled and tested. The design followed a built-in reliability approach, involving extensive finite-element simulation based analysis of the electro-thermo-mechanical strain and stress affecting the switch during both manufacturing and operation: structural simulations were carried out to identify the materials, geometry and sizes of constituent parts which would maximize reliability. Following hardware development, functional tests were carried out, showing that the module is suitable for high switching frequency operation without impairing efficiency, thus enabling a considerable reduction of system-level size and weight.